Republic of Poland : Review under the Flexible Credit Line Arrangement. (IMF Staff Country Reports; Country Report, 2014)
On January 8, 2014, the Executive Board of the IMF completed its review of Poland's qualification for the arrangement under the Flexible Credit Line (FCL) and reaffirmed Poland's continued qualification to access FCL resources. The Polish authorities have indicated that they intend to continue treating the arrangement as precautionary. The IMF has supported the authorities' policies with four successive FCL arrangements. The current two-year FCL arrangement for Poland was approved by the IMF's Executive Board on January 18, 2013, in an amount of SDR 22 billion (about USD 33.7 billion). Poland's first FCL arrangement was approved May 6, 2009, for SDR 13.69 billion (about USD 21 billion). Successor arrangements were approved in July 2010 and in January 2011.